PENGARUH LIKUIDITAS KEUANGAN DAN DAYA SAING INDUSTRI PERTAHANAN DALAM UPAYA MEWUJUDKAN EKONOMI PERTAHANAN INDONESIA - Ajeng Alfianita Abdila; Yudi Sutrasna (LPPM Institut Pendidikan Nusantara Global, 2022)
Rapid global changes and in an effort to create independence in the fulfillment of the domestic Defense and Security Forces make the defense industry must be able to maintain and increase competitive advantage. In the perspective of effective and efficient management, a company with good performance can describe the company as having a competitive advantage and competitiveness. However, based on data on the fulfillment of the main weaponry system, each stage is still below the target that was determined late. For this reason, the purpose of this study is to find out how liquidity conditions and the competitiveness of the domestic defense industry contribute to the fulfillment of the Minimum Essential Force (MEF). Liquidity is the company's ability to pay its obligations. Financial liquidity analysis is used in this study using the financial statements of PT. Pindad (Persero), PT. Dahana (Persero), and PT. Industri Telekomunikasi Indonesia (Persero complete published core during the 2015-2019 period. The effect of good liquidity can be an indicator of companies in making decisions, meeting the needs of domestic military goods and even being able to export abroad so as to create competitiveness between countries and can create national resilience.